Clinical and Onychoscopic Nail Findings in Preschool Children: An Observational Study - Ekalavya Bilkhiwal; Arun C Inamadar; Ajit B Janagond (Wolters Kluwer Medknow Publications, 2024)
Background: Nail examination plays a critical role in dermatologic conditions. Children with nail changes involve fewer physician consultations. Nail signs in early childhood can indicate the presence of a syndrome or underlying systemic disorder. Aim: The aim of the study was to investigate the frequency of nail findings in patients under 5 years of age. Subjects and Methods: The study involved 368 pediatric patients under the age of 5 years. It was an observational study conducted in dermatology, obstetrics and gynecology, and pediatric departments. A Dermlite handyscope FFH2 (×10 zoom) was used to magnify visible nail changes during a comprehensive nail examination. Results: Out of 368 cases, 213 were male and 155 were female. The average age of the patients was 22.74 months (range: 0-60). Nail findings were observed in 130 (35.3%) patients. In the study, single nail changes were observed in 123 (33.42%), whereas multiple nail changes were seen in 5 (1.35%) patients. The most common clinical nail finding was white striations in 60 (16.3%) cases, followed by punctate leukonychia in 21 (5.7%), onychoschizia in 13 (3.5%), pseudohypertrophy of the hallux in 12 (3.3%), koilonychia in 7 (1.9%), Beau's lines in 3 (0.8%), and subungual hematoma in 3 (0.8%) cases. Median canaliform nail dystrophy, Muehrcke's lines, onychophagia, and pitting were found in only one case each (0.3%). Conclusion: Physiological nail findings were more prevalent than pathological ones. The use of an onychoscope facilitated a more precise identification of nail changes by highlighting their features.